Polychaeta from several localities in the western Indian Ocean - Day, J. H. (Proceedings of the Zoological Society of London, 1962)
Two collections were examined. The first made by Dr MacGregor comes from various localities in Natal, Madagascar, Mauritius, tropical East Africa and Aden. The second made by Dr M. Kalk and Dr W. Macnae comes from Mocambique and Madagascar. Ninety-seven species are represented. Three new genera and five new species are described, several new combinations are proposed and many new records are given. The types and Dr MacGregor's collection have been deposited in the British Museum.
Kristian Fauchald's Polychaeta DB